2001
DOI: 10.1097/00129492-200103000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Middle Ear Prosthesis Displacement in High-Strength Magnetic Fields

Abstract: Middle ear prostheses made from low-magnetic stainless steel do move in the presence of high magnetic fields ex vivo; however, this does not appear to be clinically or statistically significant in vivo at 4.7 T. Magnetic resonance imaging should be undertaken with caution in individuals with prostheses made from stainless steel with strong ferromagnetic properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 10 publications
0
30
0
Order By: Relevance
“…Biomechanically and histologically completely different from the original, allograft ossicles made of stainless steel, titanium, glass ceramics and Plastipore not surprisingly have a signifi cant incidence of extrusion, may incite infection and foreign body reaction in the middle ear [20,21] . Diagnostic imaging may be hindered by ferromagnetic ossicle prostheses [22] . Even the highly biocompatible hydroxyapatite is being degraded by macrophages and multinucleated giant cells [23] .…”
Section: Discussionmentioning
confidence: 99%
“…Biomechanically and histologically completely different from the original, allograft ossicles made of stainless steel, titanium, glass ceramics and Plastipore not surprisingly have a signifi cant incidence of extrusion, may incite infection and foreign body reaction in the middle ear [20,21] . Diagnostic imaging may be hindered by ferromagnetic ossicle prostheses [22] . Even the highly biocompatible hydroxyapatite is being degraded by macrophages and multinucleated giant cells [23] .…”
Section: Discussionmentioning
confidence: 99%
“…1.5 T are becoming more common in research and clinical institutions worldwide (8)(9)(10)(11). Although studies have been conducted to evaluate the safe exposure of implant patients to MRI (8)(9)(10)(11)(12)(13)(14)(15)(16)(17), to our knowledge, no studies have been conducted to assess the safe exposure of elderly implant patients and those who have suffered a past or current episode of infection involving the implant site to MRI. This study tested the strength of human cardiac valve annulus tissue ex vivo in order to determine the forces required to cause partial or total detachment of a heart valve from the surrounding tissue, i.e., valve dehiscence.…”
Section: Introductionmentioning
confidence: 99%
“…In a study presented by Williams et al (6), an in vivo cadaver TB model demonstrated no displacement of prostheses made from nonferromagnetic stainless steel. In a recent animal study presented by Syms (8), where the Note that none of the prostheses moved in the l.5-T, but all moved in the 9.4 T-MRI scanner.…”
Section: Discussionmentioning
confidence: 96%
“…Williams et al (6) observed no deflections on their suspended string models when titanium was tested. No induced force on titanium prostheses was found by Martin et al (7) in a 3-T MR field; in addition, it was shown, using a new commercially available Fluoroptic thermometer (Luxtron, Santa Clara, CA), that no heating occurred in the titanium prostheses.…”
Section: Discussionmentioning
confidence: 97%